2022
DOI: 10.1186/s10020-022-00530-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory macrophages interrupt osteocyte maturation and mineralization via regulating the Notch signaling pathway

Abstract: Background It is well-known that both macrophages and osteocytes are critical regulators of osteogenesis and osteoclastogenesis, yet there is limited understanding of the macrophage-osteocyte interaction, and how their crosstalk could affect bone homeostasis and mineralization. This research therefore aims to investigate the effects of macrophage polarization on osteocyte maturation and mineralization process. Methods A macrophage-derived condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…A large number of macrophages with different activation states were observed in the synovium of OA patients at different stages ( Yin J. et al, 2022 ; Jia et al, 2022 ). Among them, M1 phenotype macrophages are the main subgroups of inflammatory cytokines production, cartilage degradation, and osteophyte formation in the OA state, while M2 type macrophages have a protective effect on OA by secreting some anti-inflammatory factors ( Lv et al, 2022 ; Wang et al, 2022 ). Previous studies demonstrated that inhibiting macrophages conversion to M1 type and promoting its polarization to M2 phenotype can alleviate the synovitis and delay the progress of OA ( Zhang et al, 2018 ; Li D. et al, 2022 ; Wang and He, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of macrophages with different activation states were observed in the synovium of OA patients at different stages ( Yin J. et al, 2022 ; Jia et al, 2022 ). Among them, M1 phenotype macrophages are the main subgroups of inflammatory cytokines production, cartilage degradation, and osteophyte formation in the OA state, while M2 type macrophages have a protective effect on OA by secreting some anti-inflammatory factors ( Lv et al, 2022 ; Wang et al, 2022 ). Previous studies demonstrated that inhibiting macrophages conversion to M1 type and promoting its polarization to M2 phenotype can alleviate the synovitis and delay the progress of OA ( Zhang et al, 2018 ; Li D. et al, 2022 ; Wang and He, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the importance of macrophages in osteoimmunomodulation during bone regeneration cannot be overlooked [ 48 ]. CM derived from M1 macrophages could significantly inhibit osteo-/angiogenic differentiation by releasing pro-inflammatory factors [ 49 51 ]. In our study, we revealed that the CM collected from M1 macrophages induced by Pg.LPS indeed could inhibit osteo-/angiogenesis of PDLSCs as well as the application of quercetin reversed the above inhibitory effects, providing an optimal osteoimmunomodulatory microenvironment for PDLSCs in vitro and leading to immune-enhanced osteo-/angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, M1 macrophages dominate in the early stage of inflammation, enhancing the early commitment and recruitment of angiogenic and osteogenic precursors. In contrast, M2 macrophages function in the later stage of bone regeneration by facilitating osteocyte maturation and determining the microstructure of the newly formed bone tissue [ 140 ]. Therefore, a highly orchestrated immune response comprising sequential activation of M1 and M2 macrophages is essential for subsequent bone healing [ 141 ].…”
Section: Applications Of Nps In Osteoimmunomodulationmentioning
confidence: 99%